2003
DOI: 10.1016/j.jenvman.2003.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Wildfire effects on hiking and biking demand in New Mexico: a travel cost study

Abstract: We use a travel cost model to test the effects of wild and prescribed fire on visitation by hikers and mountain bikers in New Mexico. Our results indicate that net benefits for mountain bikers is $150 per trip and that they take an average of 6.2 trips per year. Hikers take 2.8 trips per year with individual net benefits per trip of $130. Both hikers' and mountain bikers' demand functions react adversely to prescribed burning. Net benefits for both groups fall as areas recover from prescribed burns. Because bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 13 publications
2
71
0
Order By: Relevance
“…If the assumption of equidispersion holds, standard regression packages can be used to estimate a Poisson model adjusted for both truncation and endogenous stratification, as shown by Shaw (1988), by simply running a plain Poisson regression on the dependent variable modified by subtracting 1 from each of its values (Haab & McConnell, 2002, p. 174-181). This model has been used in several applied studies under the assumption of no significant overdispersion (Fix & Loomis, 1997;Hesseln et al, 2003;Hagerty & Moeltner, 2005;Martínez Espiñeira et al, 2006).…”
Section: Endogenous Stratificationmentioning
confidence: 99%
“…If the assumption of equidispersion holds, standard regression packages can be used to estimate a Poisson model adjusted for both truncation and endogenous stratification, as shown by Shaw (1988), by simply running a plain Poisson regression on the dependent variable modified by subtracting 1 from each of its values (Haab & McConnell, 2002, p. 174-181). This model has been used in several applied studies under the assumption of no significant overdispersion (Fix & Loomis, 1997;Hesseln et al, 2003;Hagerty & Moeltner, 2005;Martínez Espiñeira et al, 2006).…”
Section: Endogenous Stratificationmentioning
confidence: 99%
“…Loomis et al (2001) examined the temporal effects of fires on the welfare of recreationists in Colorado and found that their annual consumer surplus was much higher after a crown fire than following a non-crown fire or for the pre-fire forest condition. Hesseln et al (2003) found that recreationists would experience decreases in annual consumer surplus following a fire from the year of the fire to 40 years post fire. In contrast, Montanan recreationists' welfare was not substantially affected by crown or prescribed fire .…”
Section: Forest Fires In Mediterranean Countriesmentioning
confidence: 99%
“…Since the correction exerts two countervailing effects, its overall effect on the estimated aggregate welfare measures is ambiguous. We also collected information on the number of people in the visitor group sharing travel expenses during the current trip (partysize) as in Liston-Heyes and Heyes (1999) and Hesseln et al (2003) and the age composition of the visitor group in the current trip (Siderelis and Moore 1995).…”
Section: Model Specification and Variable Definitionsmentioning
confidence: 99%
“…This is because, as shown by Shaw (1988) it suffices to run a plain Poisson regression on the dependent variable modified by subtracting 1 from each of its values (Haab and McConnell 2002, p. 174-181). This strategy has been followed in several earlier works (Fix and Loomis 1997;Hesseln et al 2003;Loomis 2003, Bin et al 2005Hagerty and Moeltner 2005;Martínez-Espñeira et al 2006), under the assumption that overdispersion is not significant.…”
Section: Econometric Analysismentioning
confidence: 99%